Zakat As An Instrument Of People's Economic Empowerment: A Study Of Innovative Management Models In Rural Areas - Sudoto; Muhammad Mamun (Sekolah Tinggi Agama Islam Al-Muntahy, 2024)
This study aims to examine community-based zakat management as a model for economic empowerment of the people in rural areas with a productive zakat approach that involves active community participation and the use of information technology. The method used is a descriptive qualitative research with a case study in a village in Indonesia. The data collection technique was carried out through in-depth interviews with informants consisting of zakat managers, zakat recipients, and other related parties. The collected data was analyzed using thematic analysis techniques to identify patterns and important findings related to community-based zakat management. The results of the study show that the implementation of productive zakat in villages can improve mustahik welfare if it involves collaboration with village cooperatives and the use of information technology to increase the transparency and efficiency of zakat management. Although there are several challenges in implementation, such as a lack of understanding of productive zakat among rural communities, the results of this study make an important contribution in changing the paradigm of zakat from consumptive assistance to an instrument of economic empowerment. The implication of this research is the importance of developing a more inclusive and participatory community-based zakat model to empower the village community's economy in a sustainable manner.